The Features of Structure and Functioning of the Ecosystem in Region of the Ukrainian Antarctic Station (UAS) Academician Vernadsky - Samyshev, E. Z. (Ukrainian Antarctic Journal, 2009)
Because of ecological monitoring the integral picture of structural organization of aquatic ecosystem in an insufficiently known coastal area adjoining to the Ukrainian Antarctic station is obtained in the first approaching. A structure and functioning of biota is determined by the specific response reaction of its ecologically different elements on the line of limiting factors. The known unbalanced of Antarctic plankton on trophic relationships deepens by the briefness of vegetation period, active exchange of coastal waters with the opened Ocean and contamination of environment. As a result under plenty phyto- and bacterioplankton there is weak development of mesozooplankton, and the significant share of primary matter arrives on bottom, stipulating intensive development of bottom fauna. The accumulation of heavy metals of different toxicity by organisms of mass species of phyto- and zoobenthos, macroplankton and fishes is revealed. The inhibiting impact of pollution appears in suppression of process of reproduction of krill. Its population in this region is dependent, replenishing by transport of water masses from other regions. The intensity of this replenishment and localization of maxima of number of krill determine the food conditions for organisms-consumers of these crustaceans.